Legal Action on Labour Inspection Memo in Industrial Relations in Indonesia - Ramli, Lanny; Kaban, Samuel Nikodemus (International Journal of Criminology and Sociology, 2021)
The research purpose is to study the professional relationship between workers and employers which is called industrial relations. This is motivated by the fact that workers and employers need to synergize in the process of producing goods and services for the community. In fulfilling the purpose and object of their role and activities and the quid pro quo relationship, the stakeholders pursue different interests. Employers try to earn a maximum profit by spending the least cost possible. In contrast, workers earn the maximum results with the least minimal effort. By using the socio-legal approach, the results showed that the circumstances that exist in these two different interests are prone to conflict and prone to irregularities in legislation. The government as a regulator is obliged to provide legal protection. Legal protection from the government is manifested in the role of labor inspectors, in which they have the right to conduct inspections in a preventive and repressive manner. If there is a violation, the inspectors shall issue the inspection memo. However, the implementation of the ruling of the Constitutional Court Number 7/PUU-XII/2014 results in a new problem which is an unclear execution of the said Constitutional Court ruling about the status of workers.